Systemic analysis of eeg activation response in right and left handers - Lobasyuk, B.; Bartsevich, L. (Journal of Education, Health and Sport, 2022)
Most researchers in the study of the EEG activation response studied changes in alpha activity, while the dynamics of changes in other EEG rhythms and functional interhemispheric asymmetry (FMAA) was described and analyzed to an immeasurably lesser extent. Considering electrogenesis as a systemic category, it is advisable to study the relationships between the amplitudes of EEG rhythms using multiple regression and correlation methods of analysis. The EEG was studied on practically healthy people, students, in the state of PR and OR. Lateralization (right-handed-left-handed) was determined by EEG parameters. Activation coefficients (AC) were determined by dividing the beta-2 rhythm duration index by the alpha rhythm duration index. Relationships formed between the amplitudes of EEG rhythms were studied using calculations of multiple linear regression and correlation. In own research we was show: when opening the eyes, the amplitude of alpha and beta-1 rhythms in right-handers and left-handers decreased statistically signifiantly. Changes in the parameters of beta-2 EEG rhythms when opening the eyes in right-handers were determined to be increased in the left and right hemispheres, and in left-handers only in the forehead-temporal abduction of the left hemisphere - an increase in the duration index. Indicators of theta rhythm in right-handed people decreased in the left and right hemispheres when opening the eyes, and in left-handers, changes in theta rhythm were manifested only in the crown-occiput abduction of the right abduction. The amplitude and frequency of the EEG delta rhythm in right-handers decreased in the left and right hemispheres, and the duration indices were determined to be statistically significantly increased in all leads, with the exception of the forehead-temporal of the left hemisphere, while in left-handers, changes in the delta rhythm were observed mainly in the right hemisphere and were expressed in a decrease in amplitudes and rhythm frequencies. In the study of FIA, the alpha-rhythm index of right-handers under PR conditions was determined to be negative, and in left-handers it was positive. Under conditions of operational rest, this indicator was positive for both left-handers and right-handers. When opening the eyes, the AC in most leads increased statistically significantly in both right-handers and left-handers. The regression analysis revealed that the number of statistically significant regression coefficients increased significantly in the left hemisphere in right-handers under OP conditions, while in left-handers it decreased in the right hemisphere.